Overview on the Role of E-Cadherin in Gastric Cancer: Dysregulation and Clinical Implications - Zhao, Huichen; Hu, Huihui; Chen, Beibei; Xu, Weifeng; Zhao, Jing; Huang, Chen; Xing, Yishu; Lv, Huifang; Nie, Caiyun; Wang, Jianzheng; He, Yunduan; Wang, Sai-Qi; et al. (Frontiers in Molecular Biosciences, 2021)
Gastric cancer (GC) is one of the common malignant tumors of the digestive tract. The global incidence of gastric cancer ranks fifth among malignant tumors, and the mortality rate ranks third. Due to the low rate of early diagnosis of gastric cancer in my country, about two-thirds of patients are already in the middle and advanced stages when they are diagnosed, resulting in a poor prognosis for gastric cancer and a 5-year survival rate of less than 10 %. E-cadherin is a Ca2+-dependent cell adhesion glycoprotein encoded by the CDH1 gene. Studies have shown that E-cadherin expression decreases in gastric cancer and plays a key role in tumor cell adhesion and communication, epithelial-mesenchymal transition and tumor resistance. This article mainly summarizes the function of E-cadherin and its regulatory role in the occurrence, invasion, metastasis, and drug resistance of gastric cancer. At the same time, it reveals the application of E-cadherin in the early diagnosis, prognosis, and treatment of gastric cancer as well as the E-cadherin activator. As an anti-tumor drug development status, it provides new ideas for precise treatment of gastric cancer.